The American Foreign Policy in the Middle East from 2000 to 2010 Case Study: Iraq - Lagraa ,Sliman; Belhoucine, Hadje Aissa; NEBEG, Raouf (University of Ammar Theledji -Laghouat, 2020)
During the past century, particularly after WWII. The American foreign policy had been a triggering topic for authors, scholars, and journalists, as a debatable subject to review. America was regarded as a powerful country in the world. This study tackles the shift of the American foreign policy, from isolation to the intervention strategy, and covers the main event during the cold war. The American international policy's principal aim is to build a stable world of democracy for all America's people and the global community. Thus, this study seeks to analyse American foreign policy in the Middle East. In addition, the real motives to intervene in the countries of the Middle East such as the Gulf war and Iraq. Moreover, while it is a generally acknowledged thought among scholars, this research covers the Iraq war as a case study. The study will illustrate the real motives after the US intervention in Iraq and the reasons behind the war. Demonstrates the claims of the American administrators against Saddam Hossain and the accusation he had, because of the provocations and the decisions he made toward America, especially after the incident of 9/11. The research delves into the actual causes of Iraq's invasion and the claim of Saddam's cooperation with al-Qaeda and terrorists. Furthermore, the collected data shows the massive impact of the United States on the government of Iraq in the major domains. Finally, the main objective of the study is to discuss the American foreign policy in the world, particularly the Middle East, and the original reason for the invasion of Iraq.